Human brain single-cell data reveal shared synaptic dysfunction and immune abnormality in epilepsy and Alzheimer′s disease - YU Xiaolin, ZHANG Erning, SHA Longze (Jichu yixue yu linchuang, 2025)
Objective To identify co-expressed genes and potential comorbidity mechanisms between Alzheimer′s disease(AD) and epilepsy with publicly available single-cell transcriptome sequencing data from human brains, followed by functional validation in APP/PS1 double transgenic AD mouse models expressing the chimerical Mo/HuAPP695swe amyloid precursor protein and mutant PS1-dE9 presenilin 1. Methods The single-cell transcriptome sequencing data of brain tissue from AD and epilepsy patients were collected from gene expression omnibus (GEO) database followed by cell clustering, differential expression analysis and gene ontology (GO)functional enrichment analysis using R-based tools such as Seurat and cluster Profiler and video electroencephalogram (vEEG) monitoring and Western blot experiments. Results A total of eight major brain cell types were identified, with neurons and glial cells exhibiting shared differentially expressed genes between AD and epilepsy. These co-expressed genes were significantly clustered in pathways related to metal ion homeostasis, synaptic transmission, oxidative stress, and immune activation, which suggested common pathological mechanisms involving in synaptic dysfunction and neuro-inflammation in both disorders. The vEEG recordings of APP/PS1 mouse model of AD showed 30% of mice exhibited high-frequency epileptic seizures, while 70% showed low-frequency seizure activity. Subsequent validation in the prefrontal cortex of AD mice confirmed up-regulated expression of key molecular markers (HES5, c-FOS, and RPL10A) identified through single-cell sequencing analysis. Conclusions AD and epilepsy share gene co-expression profiles and functional pathways in specific cell types. The results of research provide a theoretical support for further elucidating their comorbidity mechanisms and developing targeted therapeutic strategy.